FORMATION OF CREATIVE ABILITIES OF JUNIOR SCHOOLCHILDREN IN THE PROCESS OF ARTISTIC ACTIVITY - Boguta, Valentina (Mountain School of Ukrainian Carpaty, 2021)
The change of the educational paradigm necessitates a rethinking of the sphere of formation of the creative personality and the development of effective methods that correspond to modern theoretical principles and methodological developments. Given that the abilities developed in artistic activity are extrapolated to all other activities of the individual, the presented empirical study presents the author's method of forming the creative abilities of primary school children by means of choreographic art. To achieve this goal, theoretical (generalization of pedagogical, psychological, art scientific works, normative documents and educational publications), empirical (study, analysis and generalization of experience of children's amateur creative associations; conversations, surveys, independent characteristics, product analysis) were used. activities; pedagogical experiment) and statistical methods (method of mathematical statistics). Criteria for the formation of the studied quality justifiably chosen emotional-sensory, basic individual-functional, value-creative. The method involves a phased (motivational-perceptual, compilative-transformative, productive-creative) implementation of a system of creative tasks of "open" type (tasks-analogies, tasks for the formation of skills to interpret and improvise with dance vocabulary, tasks for self-perception, tasks for enriching dance vocabulary, tasks for mastering elementary acting skills, tasks of partial-problematic nature, tasks for mastering the basics of dance composition) with observance of necessary and sufficient pedagogical conditions (creation of pedagogically comfortable educational environment; motivation of creative interpretive and improvisational activity of primary school children in choreographic activity; use innovative forms and methods). Their interrelation in the educational process of choreographic education of children of primary school age provides a constant purposeful influence on the formation of the studied quality. Critical analysis of experimental data led to the conclusion that the effectiveness of creative plastic and figurative self expression of junior high school students depends on creating emotionally enriched situations in the choreographic creative process, providing individual trajectory of development, systematic practice in ways of transforming activities type of activity in the implementation of their own "I-concept".